Assessment of the habits of patients with non carious cervical injuries: an observational study - Pontes, Bárbara Amurim Magalhães (2021)
The objective was to evaluate the most prevalent habits in patients with non-carious cervical lesions, through an epidemiological study. This is an epidemiological study of a cross-sectional nature, in which the deleterious habits of patients with non-carious cervical lesions were observed, through the application of a questionnaire in the dental clinic at a university in Ceará. Such participants are Brazilian, aged between 18 and 60 years old and were able to answer the questions in the questionnaire. There was a prevalence of the female gender in the research. Most patients reported the habit of consuming acidic foods and having parafunctional habits. Psycho-emotional factors and oral hygiene habits were included in the research, as well as the prevalence of aspects of injuries. It was possible to notice that non-carious cervical lesions denote a wide variety of individual characteristics and multiple etiological factors that can act in the oral cavity. Therefore, it is necessary to study these injuries to prevent and control their origin process.